How economics can further the success of ecological restoration. Issue 2 (29th September 2016) - Iftekhar, Md Sayed; Polyakov, Maksym; Ansell, Dean; Gibson, Fiona; Kay, Geoffrey M.
Abstract: Restoration scientists and practitioners have recently begun to include economic and social aspects in the design and investment decisions for restoration projects. With few exceptions, ecological restoration studies that include economics focus solely on evaluating costs of restoration projects. However, economic principles, tools, and instruments can be applied to a range of other factors that affect project success. We considered the relevance of applying economics to address 4 key challenges of ecological restoration: assessing social and economic benefits, estimating overall costs, project prioritization and selection, and long‐term financing of restoration programs. We found it is uncommon to consider all types of benefits (such as nonmarket values) and costs (such as transaction costs) in restoration programs. Total benefit of a restoration project can be estimated using market prices and various nonmarket valuation techniques. Total cost of a project can be estimated using methods based on property or land‐sale prices, such as hedonic pricing method and organizational surveys. Securing continuous (or long‐term) funding is also vital to accomplishing restoration goals and can be achieved by establishing synergy with existing programs, public–private partnerships, and financing through taxation.